Potential Effect of PISA Equivalent Questions Using the Context of Aceh Traditional Houses - Uliyatul Usnul; Rahmah Johar; Hizir Sofyan (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2019)
The achievement of Indonesian students in PISA remains unsatisfactory, as evidenced by their scores that are below the baseline level set in PISA. One of the contributing factors is that Indonesian students are less trained in solving problems with characteristics such as in PISA items. Therefore, it is necessary to familiarize Indonesian students with PISA equivalent problems, but the availability of these questions is still limited, especially concerning reasoning ability. In addition, the use of context is also crucial, especially the local contexts, which can help students understand mathematical phenomena from the perspective of their life experiences. The purpose of this study was to develop the questions of PISA equivalent mathematical reasoning ability using the context of Aceh traditional houses. This research used formative evaluation type development research from Tessmer. The results of this study were 12 mathematical questions equivalent to PISA using the context of Aceh traditional house. The potential effect of the questions developed was analyzed based on the student's responses to the questionnaire, including two aspects: 1) students are interested and seriously working on the questions and 2) the students are interested in using the equivalent PISA questions in the future.